Grant for Bottle Village possible - Dana Bartholomew:::::: (Ventura County Star)
Grandma Prisbrey assembled a dream home from the dregs of the dump. Today, her landmark Bottle Village has fallen into ruin. But her bottles may have a benefactor. City Councilwoman Barbara Williamson said there is some "very serious grant money" in the works to repair "the eyesore" created by Tressa "Grandma" Prisbrey before her death 10 years ago at the age of 92.